In vivo lumbo-sacral forces and moments during constant speed running at different stride lengths - Seay, J.; Selbie, W. S.; Hamill, J. (Journal of Sports Sciences, 2008)
The aim of this study was to introduce a Newton-Euler inverse dynamics model that included reaction force and moment estimation at the lumbo-sacral (L5-S1) and thoraco-lumbar (T12-L1) joints. Data were collected while participants ran over ground at 3.8 m · s-1 at three different stride lengths: preferred stride length, 20% greater than preferred, and 20% less than preferred. Inputs to the model were ground reaction forces, bilateral lower extremity and pelvis kinematics and inertial parameters, kinematics of the lumbar spine and thorax and inertial parameters of the lumbar segment. Repeated measures ANOVA were performed on the lower extremity sagittal kinematics and kinetics, including L5-S1 and T12-L1 three-dimensional joint angles, reaction forces and moments at touchdown and peak values during impact phase across the three stride conditions. Results indicated that L5-S1 and T12-L1 vertical reaction forces at touchdown and during the impact portion of the support phase increased significantly as stride length increased (P < 0.001), as did peak sagittal L5-S1 moments during impact (P = 0.018). Additionally, the transverse T12-L1 joint moment increased as running speed increased (P = 0.006). We concluded from our findings that our model was sensitive to our perturbations in healthy runners, and may prove useful in future mechanistic studies of L5-S1 mechanics.